Echocardiographic Assessment of the Aorta: Tips and Pitfalls - Hull, Sarah C. (AORTA, 2020)
This Yale Aortic Institute lecture provides “tips and pitfalls” regarding echocardiographic assessment of the aorta.
Keywords: echocardiography; aorta; aortic imaging; aortic dissection; aortic root; ascending aorta; transthoracic echocardiography; aortic measurement; guidelines; bicuspid aortic valve